Immigration and real wages - Neary, J (Elsevier, 1989)
This paper derives conditions under which immigration may raise nominal and real wages in a small open economy. The mechanism for such a paradoxical outcome is a demand-induced increase in the prices of labour-intensive non-traded goods.